IL-21 modulates memory and exhaustion phenotype of T-cells in a fatty acid oxidation-dependent manner - Loschinski, Romy; Böttcher, Martin; Stoll, Andrej; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios (Oncotarget, 2018)
T-cell-based therapies represent a promising strategy for cancer treatment. In this context, cytokines are discussed as a bona fide instrument for fine-tuning T- cell biology. One promising candidate is the pleiotropic interleukin-21 (IL-21) with only little being known regarding its direct effects on human T-cells. Thus, we sought out to characterize the impact of IL-21 on T-cell metabolism, fitness, and differentiation. Culturing T-cells in presence of IL-21 elicited a metabolic skewing away from aerobic glycolysis towards fatty acid oxidation (FAO). These changes of the metabolic framework were paralleled by increased mitochondrial fitness and biogenesis. However, oxidative stress levels were not increased but rather decreased. Furthermore, elevated FAO and mitochondrial biomass together with enhanced antioxidative properties are linked to formation of longer lasting memory responses and less PD-1 expression. We similarly observed an IL-21-triggered induction of central memory-like T-cells and reduced levels of PD-1 on the cell surface. Taken together, IL-21 shifts T-cells towards an immunometabolic phenotype that has been associated with increased survivability and enhanced anti-tumor efficacy. In addition, our data reveals a novel interconnection between fatty acid metabolism and immune function regulated by IL 21.
EVALuna2:34164

IL-3 is essential for ICOS-L stabilization on mast cells, and sustains the IL-33-induced RORγt+ Treg generation via enhanced IL-6 induction - Drube, Sebastian; Müller, Sylvia; Weber, Franziska; Wegner, Philine; Böttcher-Loschinski, Romy; Gaestel, Matthias; Hutloff, Andreas; Kamradt, Thomas; Andreas, Nico (Immunology, 2021)
IL-33 is a member of the IL-1 family. By binding to its receptor ST2 (IL-33R) on mast cells, IL-33 induces the MyD88-dependent activation of the TAK1-IKK2 signalling module resulting in activation of the MAP kinases p38, JNK1/2 and ERK1/2, and of NFκB. Depending on the kinases activated in these pathways, the IL-33-induced signalling is essential for production of IL-6 or IL-2. This was shown to control the dichotomy between RORγt+ and Helios+ Tregs, respectively. SCF, the ligand of c-Kit (CD117), can enhance these effects. Here, we show that IL-3, another growth factor for mast cells, is essential for the expression of ICOS-L on BMMCs, and costimulation with IL-3 potentiated the IL-33-induced IL-6 production similar to SCF. In contrast to the enhanced IL-2 production by SCF-induced modulation of the IL-33 signalling, IL-3 blocked the production of IL-2. Consequently, IL-3 shifted the IL-33-induced Treg dichotomy towards RORγt+ Tregs at the expense of RORγt− Helios+ Tregs. However, ICOS-L expression was downregulated by IL-33. In line with that, ICOS-L did not play any important role in the Treg modulation by IL-3/IL-33-activated mast cells. These findings demonstrate that different from the mast cell growth factor SCF, IL-3 can alter the IL-33-induced and mast cell-dependent regulation of Treg subpopulations by modulating mast cell-derived cytokine profiles.
CRIS-Team Scopus Importer:2021-02-05
Keywords: IL-3; IL-33; immune homeostasis; mast cells; T

Impact of Nrf2 expression in reconstituting T-cells of allogeneic hematopoietic stem cell transplanted patients - Karl, Franziska; Stoll, Andrej; Böttcher-Loschinski, Romy; Böttcher, Martin; Jacobs, Benedikt; Jitschin, Regina; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (Leukemia, 2020)
CRIS-Team Scopus Importer:2020-07-31

Impact of Nrf2 expression in reconstituting T-cells of allogeneic hematopoietic stem cell transplanted patients - Karl, Franziska; Stoll, Andrej; Gamali, S.; Böttcher-Loschinski, Romy; Böttcher, Martin; Baur, Rebecca; Jacobs, Benedikt; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Inflammation-induced glycolytic switch controls suppressivity of mesenchymal stem cells via STAT1 glycosylation - Jitschin, R.; Böttcher, Martin; Saul, D.; Lukassen, Sören; Bruns, Heiko; Loschinski, Romy; Ekici, Arif Bülent; Reis, André; Mackensen, Andreas; Mougiakakos, Dimitrios (Leukemia, 2019)
Mesenchymal stem cells (MSCs) represent key contributors to tissue homeostasis and promising therapeutics for hyperinflammatory conditions including graft-versus-host disease. Their immunomodulatory effects are controlled by microenvironmental signals. The MSCs' functional response towards inflammatory cues is known as MSC-"licensing" and includes indoleamine 2,3-dioxygenase (IDO) upregulation. MSCs use tryptophan-depleting IDO to suppress T-cells. Increasing evidence suggests that several functions are (co-)determined by the cells' metabolic commitment. MSCs are capable of both, high levels of glycolysis and of oxidative phosphorylation. Although several studies have addressed alterations of the immune regulatory phenotype elicited by inflammatory priming metabolic mechanisms controlling this process remain unknown. We demonstrate that inflammatory MSC-licensing causes metabolic shifts including enhanced glycolysis and increased fatty acid oxidation. Yet, only interfering with glycolysis impacts IDO upregulation and impedes T-cell-suppressivity. We identified the Janus kinase (JAK)/signal transducer and activator of transcription (STAT)1 pathway as a regulator of both glycolysis and IDO, and show that enhanced glucose turnover is linked to abundant STAT1 glycosylation. Inhibiting the responsible O-acetylglucosamine (O-GlcNAc) transferase abolishes STAT1 activity together with IDO upregulation. Our data suggest that STAT1-O-GlcNAcylation increases its stability towards degradation thus sustaining downstream effects. This pathway could represent a target for interventions aiming to enhance the MSCs' immunoregulatory potency.
EVALuna2:35805

Mesenchymal Stromal Cells Disrupt mTOR-Signaling and Aerobic Glycolysis During T-Cell Activation - Böttcher, Martin; Hofmann, Andreas D.; Bruns, Heiko; Haibach, Martina; Loschinski, Romy; Saul, Domenica; Mackensen, Andreas; Le Blanc, Katarina; Jitschin, Regina; Mougiakakos, Dimitrios (Stem Cells, 2016)
Mesenchymal stromal cells (MSCs) possess numerous regenerative and immune modulating functions. Transplantation across histocompatibility barriers is feasible due to their hypo-immunogenicity. MSCs have emerged as promising tools for treating graft-versus-host disease following allogeneic stem cell transplantation. It is well established that their clinical efficacy is substantially attributed to fine-tuning of T-cell responses. At the same time, increasing evidence suggests that metabolic processes control T-cell function and fate. Here, we investigated the MSCs' impact on the metabolic framework of activated T-cells. In fact, MSCs led to mitigated mTOR signaling. This phenomenon was accompanied by a weaker glycolytic response (including glucose uptake, glycolytic rate, and upregulation of glycolytic machinery) toward T-cell activating stimuli. Notably, MSCs express indoleamine-2,3-dioxygenase (IDO), which mediates T-cell suppressive tryptophan catabolism. Our observations suggest that IDO-induced tryptophan depletion interferes with a tryptophan-sufficiency signal that promotes cellular mTOR activation. Despite an immediate suppression of T-cell responses, MSCs foster a metabolically quiescent T-cell phenotype characterized by reduced mTOR signaling and glycolysis, increased autophagy, and lower oxidative stress levels. In fact, those features have previously been shown to promote generation of long-lived memory cells and it remains to be elucidated how MSC-induced metabolic effects shape in vivo T-cell immunity. Stem Cells 2016;34:516-52
EVALuna2:25707

Monitoring of the immunometabolic profile of reconstituting leukocytes upon autologous peripheral blood stem cell transplantation - Richter, Swetlana; Jacobs, Benedikt; Böttcher, Martin; Stoll, Andrej; Böttcher-Loschinski, Romy; Mackensen, Andreas; Mougiakakos, Dimitrios (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Oxidative stress upon allogeneic hematopoietic stem cell transplantation and its impact on the reconstituting immune system - Karl, Franziska; Böttcher-Loschinski, Romy; Stoll, Andrej; Rösler, Wolf; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Palmitoylated Proteins on AML-Derived Extracellular Vesicles Promote Myeloid-Derived Suppressor Cell Differentiation via TLR2/Akt/mTOR Signaling - Tohumeken, Sehmus; Böttcher, Martin; Stoll, Andrej; Loschinski, Romy; Panagiotidis, Konstantinos; Braun, Martina; Saul, Domenica; Baur, Andreas; Bruns, Heiko; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios; et al. (Cancer Research, 2020)
Acute myeloid leukemia (AML) represents the most common acute leukemia among adults. Despite recent progress in diagnosis and treatment, long-term outcome remains unsatisfactory. The success of allogeneic stem cell transplantation underscores the immunoresponsive nature of AML, creating the basis for further exploiting immunotherapies. However, emerging evidence suggests that AML, similar to other malignant entities, employs a variety of mechanisms to evade immunosurveillance. In light of this, T-cell inhibitory myeloid-derived suppressor cells (MDSC) are gaining interest as key facilitators of immunoescape. Accumulation of CD14(+) HLA-DRlow monocyticMDSCs has been described in newly diagnosed AML patients, and deciphering the underlying mechanisms could help to improve anti-AML immunity. Here, we report that conventional monocytes readily takeup AML-derived extracellular vesicles (EV) and subsequently undergo MDSC differentiation. They acquired an CD14(+)HLA-DRlow phenotype, expressed the immunomodulatory indoleamine-2,3-dioxygenase, and upregulated expression of genes characteristic for MDSCs, such as S100A8/9 and cEBP beta. The Akt/mTOR pathway played a critical role in the AML-EV-induced phenotypical and functional transition of monocytes. Generated MDSCs displayed a glycolytic switch, which rendered them more susceptible toward glycolytic inhibitors. Furthermore, palmitoylated proteins on the AML-EV surface activated Toll-like receptor 2 as the initiating event of Akt/mTOR-dependent induction of MDSC. Therefore, targeting protein palmitoylation in AML blasts could block MDSC accumulation to improve immune responses.
CRIS-Team WoS Importer:2020-09-25

Profiling extracellular vesicles (EV) in patients with acute GvHD after allogeneic stem cell transplantation - Böttcher, Martin; Stoll, Andrej; Böttcher-Loschinski, Romy; Rösler, Wolf; Winkler, Julia; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon; Baur, Rebecca (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23